2009
DOI: 10.1017/s0033822200033774
|View full text |Cite
|
Sign up to set email alerts
|

Six Decades of Radiocarbon Dating in New World Archaeology

Abstract: ABSTRACT. Radiocarbon ( 14 C) dating provided New World archaeological research with the first continent-wide common chronometric scale that transcended the mostly relative site-and region-specific chronological sequences that had been assembled during the preceding century of fieldwork. 14 C data continue to play a critical role in establishing a chronometric framework for the 5-century-long debate concerning the timing of the initial peopling of the New World. Other issues where 14 C results have been of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 153 publications
0
10
0
Order By: Relevance
“…Stafford et al 1991). This situation is evident from the radiocarbon dating of the Kennewick and Anzick remains in North America (Taylor 2009). For the latter, the use of different amino acids and bulk collagen resulted in ages between c .…”
Section: Which Of the Bone Dating Materials Is The Most Reliable?mentioning
confidence: 98%
“…Stafford et al 1991). This situation is evident from the radiocarbon dating of the Kennewick and Anzick remains in North America (Taylor 2009). For the latter, the use of different amino acids and bulk collagen resulted in ages between c .…”
Section: Which Of the Bone Dating Materials Is The Most Reliable?mentioning
confidence: 98%
“…She was 80% intact and was considered to be in fair taphonomic condition (Gonz alez et al, 2008). Radiocarbon dating of amino acids indicated that the remains were from 13.4 to 13.8 Ka (Gonz alez et al, 2013) although the age has been questioned due to the leaching and degradation of amino acids necessary to calculate an accurate date (Chatters et al, 2014;Taylor, 2009). No primary environmental data were collected to assess its taphonomic history or the skeletal age.…”
Section: Paleoamerican Remains In Hoyo Negromentioning
confidence: 99%
“…Hard-water effects and collagen leaching result in contamination which can make dating difficult (e.g. Dixon, 1999;Gonz alez et al, 2008;Taylor, 2009). Dating of associated artifacts can be used, but is problematic, particularly in HN, were there is little sediment coverage to provide any stratigraphic association or context (Chatters, 2000;Chatters et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…The absolute dating was accomplished by using different radiometric techniques (AMS and U/Th), both on bone and on charcoal. However, AMS dates on human bones must be taken with caution, as the amount of preserved collagen is very small in these cases [48], which can affect the accuracy of the date. For example, the Las Palmas individual was dated to 8,050+/-130 BP using AMS, and to 12,000-10,000 BP using U/Th techniques, illustrating the range of possible error.…”
Section: The Early Human Remains From Quintana Roomentioning
confidence: 99%